Approaching the poem “Deshora” by César Vallejo - Ángeles Escobar, Alejandro Raúl (Espergesia, 2017)
This essay has dealt with a very important stage in César Vallejo’s life: puberty/adolescence, a theme that the poet sets forth in the poem “Deshora” (Los Heraldos Negros, 1919). Our purpose has been to describe the poet´s contradictory feelings, when referring to puberty. In addition, the poet´s feelings and emotions have been interpreted in relation to the beloved, admired, and remembered purity that his eyes could never enjoy. Through a conscientious analysis of the poem, which was the object of study, this work is introduced in it, following the poetic voice in his contradictory memories, accompanied by a discouraging and painful feeling.